Oxidative stress markers in patient-derived non-cancerous cervical tissues and cells - Katerji, Meghri (Sci Rep, 2020)
High-risk human papillomaviruses (HPV) are the causative agents of cervical cancer. However, not all infected women develop cervical cancer. Cervical tumorigenesis is characterized by a multifactorial etiology, with oxidative stress (OS) likely playing a major role. In addition to exogenous sources, metabolic processes also contribute to OS. In principle, variability in levels of cervical OS has the potential to influence the likelihood of conversion to cervical cancer. To ask whether such variability indeed existed, we assessed the levels of ROS and the oxidative DNA damage biomarker 8-oxodG in normal non-cancerous cervical tissues and cells obtained from women with uterovaginal pelvic organ prolapse following vaginal hysterectomy. We demonstrated five and ten-fold variability between tissues isolated from the transformation zone (TZ) and ectocervix (EC) of different women, respectively. Despite the greater variability (likely due to differences in tissue composition), the overall pattern of ROS levels in EC tissues mirrored those obtained in their corresponding TZ tissues. Our results also show that the levels of ROS in TZ tissues were always higher than or equal to those found in the respective EC tissues, providing a possible explanation for TZ tissue being the primary target for HPV infection and cervical carcinogenesis. Interestingly, primary keratinocytes isolated and cultured from these cervical specimens also displayed high variability in ROS levels, with some strongly mirroring the levels of ROS observed in their corresponding tissues, while others were less closely associated. Finally, we demonstrated that the levels of DNA damage mirrored the levels of ROS in the cultured primary cells. Understanding the factors and mechanisms that dispose certain individuals to develop cervical cancer has the potential to enable the development of approaches that make the conversion of HPV infection to cancer development even more rare.